Effects of C‐Terminal Amelogenin Peptide on Proliferation of Human Cementoblast Lineage Cells. Issue 7 (1st July 2016) - Yoshimi, Yuki; Kunimatsu, Ryo; Hirose, Naoto; Awada, Tetsuya; Miyauchi, Mutsumi; Takata, Takashi; Li, Wu; Zhu, Li; Denbesten, Pamela; Tanne, Kazuo; Tanimoto, Kotaro
Abstract : Background: Extracts of enamel matrix proteins are used to regenerate periodontal tissue; amelogenin, the most abundant enamel protein, plays an important role in this regeneration. Studies have demonstrated that amelogenin fragments promote tissue regeneration, but the bioactive site of amelogenin remains unclear. This study explores the functional domain of amelogenin by investigating effects of four amelogenin species on cementoblast proliferation. Methods: Four amelogenin species based on amelogenin cleavage products were investigated: 1) recombinant human full‐length amelogenin (rh174); 2) amelogenin cleavage product lacking the C‐terminal (rh163); 3) amelogenin cleavage product lacking the N‐terminal (rh128); and 4) the C‐terminal region of rh174 (C11 peptide), which was synthesized and purified. Human cementoblast‐like cell line (HCEM) cells were cultured and treated with rh174, rh163, rh128, or C11 peptide. Cell proliferation was evaluated using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐ tetrazolium assay and cell proliferation enzyme‐linked immunosorbent assay. Mitogen‐activated protein kinase (MAPK)–extracellular signal‐regulated kinase (ERK) (MAPK–ERK) pathway was examined by Western blot analysis. Results: Proliferation of HCEM cells was significantly enhanced on treatment with rh174, rh128, or C11 peptide. However, rh163 had no effect compared with the untreated control group. Western blot analysis revealed enhanced phosphorylated ERK1/2 signaling after addition of rh128 or C11 peptide and reduced phosphorylated ERK1/2 signaling after blocking with a specific MAPK inhibitor (U0126). Conclusion: C‐terminal amelogenin cleavage product increased proliferation of HCEM through MAPK–ERK signaling pathway, indicating possible application of C11 peptide for periodontal tissue regeneration.